ISLAM MENGUTAMAKAN ILMU PENGETAHUAN DAN TEKNOLOGI - Yedi Purwanto (Fakultas Seni Rupa dan Desain ITB, 2011)
Islam Prioritize to the role of science, technology and art in the advancement of civilization and the Islamic da'wah. Muslims are required to master these three things that can lead to world civilization. This is reflected in a series of revelations received by Prophet Muhammad SAW for the first time that the letter of Al-Alaq paragraphs 1 to 5. Afzalur Rahman in